Feasibility of shear wave elastography for assessing steatosis in early-stage non-alcoholic fatty liver disease - Hui Jiang; Chuan Qin; Yue-Mei Xu (PLoS ONE, 2025)
Non-alcoholic fatty liver disease (NAFLD) is characterized by hepatic fat accumulation with varying degrees of severity. This study aimed to evaluate the feasibility of shear wave elastography (SWE) for assessing the grade of liver steatosis in early-stage NAFLD without fibrosis. A total of 260 subjects were categorized into four groups of G0 (n = 81), G1 (n = 63), G2 (n = 54), and G3 (n = 62). Conventional ultrasound and point SWE examinations were used to assess the grade of liver steatosis in varies degrees and compared with MRI-proton density fat fraction (MRI-PDFF), which was used to quantify hepatic fat content. SWE demonstrated high reproducibility across all groups with interclass correlation coefficients ranging from 0.80 to 0.94. The correlation between SWE and MRI-PDFF were 0.68, 0.71, 0.68 and 0.53 for G0-G3 NAFLD. For conventional ultrasound, the diagnostic performance were 0.77 (95% CI: 0.71–0.83), 0.76 (95% CI: 0.71–0.82), 0.76 (95% CI: 0.70–0.83), for G0 versus G1-3, G0-1 versus G2-3, and G0-2 versus G3. For SWE, the diagnostic performance were 0.88 (95% CI: 0.84–0.92), 0.86 (95% CI: 0.81–0.90), and 0.81 (95% CI: 0.75–0.87), for G0 versus G1-3, G0-1 versus G2-3, and G0-2 versus G3. The SWE showed better diagnostic performance than conventional ultrasound in G0 versus G1-3 (p = 0.003), G0-1 versus G2-3 (p = 0.002), but not in G0-2 versus G3 (p = 0.262). SWE is a reliable tool for assessing the grade of liver steatosis, which could be a valuable tool for monitoring and grading NAFLD in early-stage.